INDEKS KEPUASAN MASYARAKAT TERHADAP INOVASI PELAYANAN PUBLIK PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN SUMBAWA - Saputra, Yosi; Sutrisno, Eko (Jurnal Ekonomi & Bisnis, 2025)
This study aims to know the public satisfaction index related to public service innovation at Department of Planting Capital and One Stop Integrated Service. The type of data used in this study was quantitative data obtained from primary sources. Data collection in this study used a research instrument in the form of a questionnaire. The respondents in this study were 96 users of public services at Department of Planting Capital and One Stop Integrated Service of Sumbawa District. Respondent selection used non-probability sampling techniques with the accidental sampling method. The data was analyzed using the public satisfaction index analysis technique and interpreted based on the categories stipulated in the Minister of PAN-RB Regulation Number 14 of 2017. The results of this study showed that the level of public satisfaction on services at Department of Planting Capital and One Stop Integrated Service of Sumbawa District was in the Good category. This means that in general the public feels satisfied with the services provided by Department of Planting Capital and One Stop Integrated Service of Sumbawa District. The services provided by Department of Planting Capital and One Stop Integrated Service of Sumbawa District have met the expectations of most of the people who use these services.